The little sea horse - Cresswell, Helen; Cockcroft, Jason (Hodder London, 1995)
A tiny pure white horse with golden hooves has come out of the sea; Molly knows he is far too precious to keep, but the local townspeople lock the magical horse in a cage. Only Molly can find a way to release him back to the sea. Suggested level: primary, intermediate